Effect of Molecular Architecture on Conformational Relaxation of Polymer Chains at Interfaces. Issue 21 (27th May 2020) - Nguyen, Hung K.; Kawaguchi, Daisuke; Tanaka, Keiji
Abstract: Dynamics of polymer chains near an interface with an inorganic material are believed to strongly affect the physical properties of polymers in nanocomposites and thin films. An effect of molecular architecture on the conformational relaxation behavior of polystyrene (PS) chains at the quartz interface using sum‐frequency generation spectroscopy is reported here. The relaxation dynamics of chains in direct contact with the quartz interface is slower with a star‐shaped architecture than that with its linear counterpart. The extent of the delay becomes more pronounced with increasing number of arms. This can be explained in terms of the superior interfacial activity to the quartz surface for the star‐shaped PS. Abstract : An effect of molecular architecture on the relaxation dynamics of polystyrene chains at the quartz interface is examined using sum‐frequency generation (SFG) spectroscopy. Star‐shaped polystyrene in direct contact with the interface relaxes more slowly than its linear counterpart, and the extent of the slow‐down increases with increasing arm functionality.